Analisis dampak penggunaan smartphone untuk bermain game pada motivasi belajar peserta didik kelas vi sekolah dasar - Muhammad Sulthan Malik Azzukhruf; Sri Marmoah; Tri Budiharto (Didaktika Dwija Indria, 2022)
The purpose of this research is find out  the impacts of smartphone usage for playing games to learning motivation on VI grade student of 1 Krapyak Elementary School Jepara. This research used a descriptive qualitative method. The sample are collected by makeshift sampling. The data are collected through observing, questionnaire, interviewing, and documenting. The validity of research data used triangulation of data. Data were analyzed by data reduction, data presentation, and drawing conclusions. The results showed that positive and negative impacts of playing games could affect the learning motivation on students. There are four positive and five negative impacts of smartphone usage for playing games. The positive impacts are cognitive improved, social ability improved, learned from games, and entertained. The negative impacts are affect health, said harshly, misbehave, decreased school grade, and lazy. The duration of playing games could affect how much positive and negative impact on students. The conclusion of this research is the impacts of smartphone usage for playing games can affect learning motivation on VI grade student of 1 Krapyak Elementary School Jepara.